The Effect of Religious Awareness as a Therapeutic Medium on the Shaping Students' Religious Behavior - Fiki Prayogi; Palasara Brahmani Laras; Yasin Adam (International Journal of Counseling and Psychotherapy, 2025)
Background: Religious awareness is a key factor in shaping students’ religious behavior, especially during the formative years of primary school amid growing moral and spiritual challenges. Objective: This study aims to determine the effect of religious awareness as a moderator in shaping the religious behavior of primary school students. Method: A correlation study was conducted at SMA Adiguna Bandar Lampung during the 2023/2024 academic year. The research involved 80 randomly selected students. Data were collected using religious awareness and religious behavior scales. Instrument validity was tested using the product-moment formula, while reliability was assessed with Cronbach’s alpha. Data analysis employed the product-moment formula. Result: The findings indicate a positive relationship between religious awareness and religious behavior, demonstrating that religious awareness significantly influences students' religious life. Conclusion: Religious awareness plays a critical role in moderating and shaping students' religious behavior. It suggests that fostering higher levels of religious awareness can positively influence students’ religious actions and attitudes, potentially leading to a more spiritually engaged and conscientious student body. Contribution: This study provides novel insights and scientific information regarding the mediating role of religious awareness in fostering students' religious behavior.